2003
DOI: 10.1002/hbm.10128
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory cortical activation observed by fMRI during a cognitive task at the earliest stage of multiple sclerosis

Abstract: Recent functional magnetic resonance imaging (fMRI) studies have suggested that functional cortical changes seen in patients with early relapsing-remitting multiple sclerosis (MS) can have an adaptive role to limit the clinical impact of tissue injury. To determine whether cortical reorganization occurs during high cognitive processes at the earliest stage of multiple sclerosis (MS), we performed an fMRI experiment using the conventional Paced Auditory Serial Addition Test (PASAT) as paradigm in a population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
174
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(208 citation statements)
references
References 62 publications
27
174
0
7
Order By: Relevance
“…Since only the corrected answers were modelled in the statistical analysis and task performance was similar between patients and controls, we can reasonably rule out a possible influence of cognitive impairment and different task performance between patients and controls on our fMRI results. These results are in agreement with those of previous studies which assessed fMRI patterns of activation during the performance of cognitive tasks in patients at the earliest stages of the disease [Audoin et al, 2003] and in those with relapsing course [Hillary et al, 2003;Mainero et al, 2004;Staffen et al, 2002]. Our results are partially in contrast with those of a previous study [Parry et al, 2003] of a mixed group of patients with relapsing remitting (RR) and secondary progressive (SPM) MS, where an increased activation of the L frontal cortex and a decreased activation of the R frontal cortex were found in patients in comparison with controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Since only the corrected answers were modelled in the statistical analysis and task performance was similar between patients and controls, we can reasonably rule out a possible influence of cognitive impairment and different task performance between patients and controls on our fMRI results. These results are in agreement with those of previous studies which assessed fMRI patterns of activation during the performance of cognitive tasks in patients at the earliest stages of the disease [Audoin et al, 2003] and in those with relapsing course [Hillary et al, 2003;Mainero et al, 2004;Staffen et al, 2002]. Our results are partially in contrast with those of a previous study [Parry et al, 2003] of a mixed group of patients with relapsing remitting (RR) and secondary progressive (SPM) MS, where an increased activation of the L frontal cortex and a decreased activation of the R frontal cortex were found in patients in comparison with controls.…”
Section: Discussionsupporting
confidence: 93%
“…The conventional SPM analysis exclusively showed an increased activation of all the previous areas in BMS patients when contrasted to controls, thus not allowing to disclose any difference in the behaviour of the different areas. The notion that increased recruitment of areas of the R hemisphere is a critical aspect for a reorganisation inside the cognitive network is in line with previous activation [Audoin et al, 2003;Hillary et al, 2003;Mainero et al, 2004;Staffen et al, 2002] and connectivity studies [Cader et al, 2006] performed on patients with clinically isolated syndromes suggestive of MS and RRMS, as well as with many studies of the motor network [Filippi and Rocca, 2004] showing that recruitment of homologous regions in the two hemisphere is one of the main compensatory mechanisms, at least at the beginning of the disease. This is the first study showing that this mechanism is working also in patients with BMS.…”
Section: Discussionsupporting
confidence: 85%
“…Working memory has been the most extensively studied domain by means of the Paced Auditory Serial Addition Test (PASAT) or the Paced Visual Serial Addition Task. [7][8][9][10][11][12][13] In patients with a clinically isolated syndrome (CIS) suggestive of MS, an altered pattern of cortical activations has been described during PASAT performance, confirming the presence of cortical reorganization at the earliest clinical stage of disease. 10 An increased recruitment of several cortical areas during PASAT has also been shown in patients with relapsing-remitting (RR) MS and mild cognitive impairment, 11 suggesting that an impaired cognitive task performance in these patients could reflect a decreased function of canonical task-specific areas in the absence of adequate compensatory strategies.…”
Section: Active Cognitive Tasksmentioning
confidence: 88%
“…At later stages, bilateral activation of these regions is first observed, followed by a widespread recruitment of additional areas, which are usually recruited by healthy subjects in the performance of more complex or novel tasks . Similarly, fMRI studies investigating various cognitive domains in MS patients have shown altered patterns of cortical activation (Audoin et al, 2003;Staffen et al, 2002;Hillary et al, 2003;Li et al, 2004;Cader et al, 2006). Moreover a relationship between cortical activation and fatigue has been shown in several studies suggesting that the underlying mechanism of this common but poorly understood symptom may be the deficiency of neuronal compensation (Filippi et al, 2002;White et al, 2009).…”
Section: Functional Mrimentioning
confidence: 98%